Metode Fun Learning Sebagai Upaya Peningkatan Pemahaman Konsep Perkenalan Diri Siswa Kelas 1 SDN Sawentar 02 Kabupaten Blitar - Eny Rosidah (Edukasia, 2021)
Abtract: Learning in the lower class is carried out based on the lesson plans that have been developed by the teacher. The learning process must be designed by the teacher so that students' abilities, teaching materials, learning processes, and assessment systems are in accordance with the stages of student development. Another thing that must be understood is that the learning process must be developed interactively and fun. At SDN Sawentar 02 Kanigoro District, Blitar Regency, learning in grade 1 in terms of online self-introduction, it can be seen that it has not yet reached completeness. Of the 20 students who achieved completeness only 6 students or 30%, of this there needs to be an improvement in learning. For this reason, researchers conducted classroom action research quantitatively and qualitatively, to solve these problems. Researchers use the Fun Learning learning method, which is a strategy used to create an effective learning environment, implement curriculum, deliver material, facilitate the learning process which results in improved student learning achievement.